Substance Flow Analysis in Finland – Four Case Studies on N and P Flows - Antikainen, Riina (Finnish Environment Institute, 2013)
Nitrogen (N) and phosphorus (P) are essential elements for all living organisms.However, in excess, they contribute to such environmental problems as aquatic and terrestrial eutrophication (N, P), acidification (N), global warming (N), groundwater pollution (N), depletion of stratospheric ozone (N), formulation of tropospheric ozone (N) and poor urban air quality (N). Globally, human action has multiplied the volume of N and P cycling since the onset of industrialization. Themultiplication is a result of intensified agriculture, increased energy consumption and population growth. Industrial ecology (IE) is a discipline, inwhich human interactionwith the ecosystems is investigated using a systems analytical approach. The main idea behind IE is that industrial systems resemble ecosystems, and, like them, industrial systems can then be described using material, energy and information flows and stocks. Industrial systems are dependent on the resources provided by the biosphere, and these two cannot be separated from each other. When studying substance flows, the aims of the research from the viewpoint of IE can be, for instance, to elucidate theways howthe cycles of a certain substance could be more closed and how the flows of a certain substance could be decreased per unit of production (= dematerialization). IE uses analytical research tools such as material and substance flow analysis (MFA, SFA), energy flow analysis (EFA), life cycle assessment (LCA) and material input per service unit (MIPS). In Finland, N and P are studied widely in different ecosystems and environmental emissions. A holistic picture comparing different societal systems is, however, lacking. In this thesis, flows of N and P were examined in Finland using SFA in the following four subsystems: I) forest industry and use of wood fuels, II) food production and consumption, III) energy, and IV) municipal waste. A detailed analysis at the end of the 1990s was performed. Furthermore, historical development of the N and P flows was investigated in the ...